Assessment of chest pain in hypertrophic cardiomyopathy using exercise thallium-201 myocardial scintigraphy. Issue 6 (December 1980) - Pitcher, D; Wainwright, R; Maisey, M; Curry, P; Sowton, E
Abstract : Exercise thallium-201 myocardial scintigraphy was performed in 23 patients with hypertrophic cardiomyopathy. Eighteen patients presented with chest pain which was a persistent symptom in 11. Selective coronary arteriography was performed in 16 patients and showed normal coronary arteries in 15 and insignificant luminal irregularities in one patient. Eighteen patients had abnormal scintigrams. Three had an abnormal distribution of tracer entirely attributable to asymmetric septal hypertrophy, whereas 15 had discrete tracer uptake defects which could not be explained solely by myocardial hypertrophy. In this latter group of patients three scintigraphic patterns were identified: (1) in 10 patients defects were seen in scintigrams immediately after exercise but not in delayed images obtained four to six hours later. Eight of these patients had chest pain. (2) Four patients had uptake defects seen in both initial and delayed images. One patient had chest pain. (3) In three patients, one of whom had chest pain, tracer defects were seen only in delayed images and were not apparent in the initial scintigrams. Chest pain occurred in eight out of 10 patients with scintigraphic evidence of myocardial ischaemia but was present in only three out of 13 patients with non-ischaemic scintigrams. The value of exercise thallium-201 myocardial imaging as a diagnostic technique in hypertrophic cardiomyopathy appears limited. Scintigraphic evidence of regional myocardial ischaemia in the absence of significant coronary artery disease, however, contributes to an understanding of the mechanism of angina production in patients with hypertrophic cardiomyopathy.